O102 FINDING FACTORS ASSOCIATED WITH SAFE IMPLEMENTATION OF IVOR LEWIS TOTALLY MINIMALLY INVASIVE ESOPHAGECTOMY. (23rd November 2019) - ; Claassen, Linda; van Workum, Frans; Rovers, Maroeska M; Hannink, Gerjon; Rosman, Camiel
Abstract: Aim: To define factors associated with more efficient learning after implementation of Ivor Lewis totally minimally invasive esophagectomy (TMIE). Background and Methods: It is unknown which factors are associated with more efficient learning after implementation of Ivor Lewis TMIE. Prospectively collected data of 15 European expert centers are retrospectively analyzed. Consecutive patients undergoing Ivor Lewis TMIE are included. The primary outcome is anastomotic leakage and the secondary outcome is textbook outcome (TBO). The pre-defined level of acceptance for anastomotic leakage is set at 8% with a 5% margin. Trends in outcome parameters are plotted using weighted moving average to define when the pre-defined level of acceptance is reached. Outcome trends are compared between groups of hospitals for the following factors: hospital volume, surgeon experience, overall TMIE experience, expert clinic visit, Ivor Lewis TMIE course followed and Ivor Lewis TMIE proctor supervision during implementation. Results: This study included 1718 patients. Hospitals with a volume > 50 cases per year reached the pre-defined level of acceptance for anastomotic leakage at case 114, hospitals with a volume <50 cases did not reach the pre-defined level of acceptance. Hospitals with surgeon experience > 10 years and <10 years reached the pre-defined level of acceptance at case 112 and 135, respectively. Hospitals with overall TMIE experience > 50 cases and <50 cases reached the pre-defined level of acceptance at case 45 and 112, respectively. Visiting an expert clinic, followed a TMIE course, or implementation under a proctor's supervision did not contribute to reaching the level of acceptance earlier. Conclusion: Learning curves are shorter and the level of acceptance is reached earlier if Ivor Lewis TMIE is implemented in a high-volume hospital, if the procedure is implemented in a hospital with a surgeon with > 10 years of experience, or if the surgeon has experience in other types of TMIE of > 50 cases. These findings can inform surgeons and can contribute to formulate evidence-based training programs.